Surface Morphology and Strength of Chemically Treated Saccharum Officinarum Bagasse Fibres Cement Composites of Low Carbon Concrete - Norsuzailina, Mohamed Sutan; Faisal, Amsyar; Raudhah, Ahmadi; Abdul Razak, Abdul Karim; Norazzlina, M.Sa'don; Siti Noor Linda, Taib; Nur Syuhada, Ahmad Zauzi; Farah Nora Aznieta, Abd Aziz; Md. Habibur Rahman, Sobuz; Shuvo Dip, Datta; Md. Saiful, Islam; Noor Md. Sadiqul, Hasan (Construction Research Institute of Malaysia (CREAM), 2024)
This study explores the potential of Saccharum Officinarum Bagasse Fibres (SOBF) as a sustainable reinforcement in cement-based composites for affordable construction in developing countries. Focusing on locally sourced SOBF, known for its sustainability and low cost, this research aims to enhance the mechanical properties of cement composites. The study examines the impact of SOBF on compressive strength, comparing 1%, 2%, and 3% fibre content at 7 and 28 days, both treated and untreated. Scanning Electron Microscopy (SEM) analysis revealed that SOBF inclusion mitigates surface cracking through a bridging effect within the hardened cement. Results indicate that compressive strength increases up to an optimal fibre content, with 1 wt.% providing the best outcomes for both treated and untreated samples. Interestingly, untreated composites displayed higher compressive strength than their treated counterparts, likely due to the natural lignin enhancing fibre-matrix bonding. The findings demonstrate that SOBF significantly improves the mechanical properties and durability of cement composites, ideal for sustainable construction in regions prioritizing cost effectiveness and local resource utilization. This study not only highlights the benefits of integrating natural fibres like SOBF in cementitious applications but also emphasizes the importance of optimizing fibre content and treatment to enhance composite performance.